Effects of left-hand contraction on tennis serve performance - Mizuno, Kanta; Masaki, Hiroaki (Frontiers in Psychology, 2024)
Introduction The tennis serve is commonly executed in high-pressure scenarios, often leading to performance decline; a condition commonly referred to as choking under pressure. One suggested effective method to avert choking involves contracting the left hand. We examined the effects of left-hand contraction on tennis serve performance using a wearable grasping material (polyurethane foam) which can be incorporated into sportswear. Materials and methods We assigned 40 right-handed skilled tennis players to either the contraction group (n = 20) or the no-contraction group (n = 20). They were instructed to perform a second-serve task during the pre-test and pressure test. The participants in the contraction group squeezed the grasping material for 20 s before executing the task in the pressure test. We measured performance, including total scores, the number of maximum score achievements, landing positions, and kinematic indices (i.e., ball speed, racket speed, and impact height). Results Although neither group demonstrated deteriorated performance on the pressure test, the contraction group experienced an increased number of maximum score achievements under the pressure situation compared with the pre-test (p = 0.021). Discussion Our results suggest that when under pressure, left-hand contraction may improve performance during tennis serves.